Relationship between Nutritional Status and Haemoglobin Level in Students of Senior High School 3 Bone - Murfat, Zulfitriani; Rahman, Haryadi; Idrus, Hasta Handayani; Kamaluddin, Irna Diyana Kartika; B, Sri Wahyuni Gayatri (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2024)
Abstrak Latar Belakang: Status gizi adalah suatu ukuran mengenai kondisi tubuh seseorang yang dapat dilihat dari makanan yang dikonsumsi dan penggunaan zat-zat gizi dalam tubuh. Ketidakseimbangan antara status gizi dengan kebutuhan tubuh menimbulkan kelainan patologis bagi tubuh. Seperti malnutrisi akibat kurangnya asupan zat gizi sehingga kebutuhan gizi dalam tubuh tidak terpenuhi terutama kebutuhan gizi seperti zat besi. Dimana zat besi adalah salah satu komponen penting dalam pembentukan hemoglobin. Mengacu pada latar belakang tersebut penulis tertarik untuk melakukan penelitian mengenai hubungan status gizi terhadap kadar hemoglobin pada siswa/siswi SMAN 3 Bone. Metode: Metode penelitian ini adalah Observasional analitik. Dengan menentukan status gizi melalui pemeriksaan antropometri IMT dan kadar hemoglobin dengan Easy Touch GCHB. Hasil: Hasil penelitian menunjukkan dari 80 siswa/siswi memiliki status gizi underweight 31,3%, normal 46,3%, overweight 13,8%, obesitas I 7,5%, obesitas II 1,3% sedangkan pada kadar hemoglobin sebanyak 27,5% mengalami anemia dan 72,5% normal. Terdapat hubungan yang bermakna antara status gizi terhadap kadar hemoglobin sebesar 0,003 (p<0,005). Kesimpulan: Terdapat hubungan yang signifikan antara status gizi terhadap kadar hemoglobin pada siswa/siswi SMAN 3 Bone. Abstract Background: Nutritional status is a measure of the condition of a person's body that can be seen from the food consumed and the use of nutrients in the body. The imbalance between nutritional status and body needs causes pathological disorders for the body. Such as malnutrition due to lack of nutrient intake so that nutritional needs in the body are not met, especially nutritional needs such as iron. Where iron is one of the important components in the formation of hemoglobin. Referring to this background, the author is interested in conducting research on the relationship between nutritional status and hemoglobin levels in students of SMAN 3 Bone. Methods: This research method is Observational analytic. By determining nutritional status through anthropometric examination of BMI and hemoglobin levels with Easy Touch GCHB. Results: The results showed that out of 80 students had a nutritional status of underweight 31.3%, normal 46.3%, overweight 13.8%, obesity I 7.5%, obesity II 1.3% while at hemoglobin levels as much as 27.5% were anemic and 72.5% were normal. There is a significant relationship between nutritional status and hemoglobin levels of 0.003 (p<0.005). Conclusion: There is a significant relationship between nutritional status and hemoglobin levels in students of Senior High School 3 Bone.